Efficacy of bio-fertilizers and combinations with chemical fertilizers on biochemical parameters of okra (Abelmoschus esculentus (L.) Moench) (International Journal of Food and Nutritional Sciences, 2023)
The Present investigation was conducted during 2021 at Agricultureal Research Farm of Rama University , Mandhana, Kanpur (U.P), Studies on the“Efficacy of bio-fertilizer and the combinations with chemical fertilizers on chemical parameters of okra [Abelmoschus esculentus (L.) Moench]”, revealed that Acidity, Ascorbic acid and moisture percent were maximized. when we use with Recommended dose of fertilizers , NPK 40 percent, PSB 40 percent, Azotobacter 40 percent and Azospirillum 65 percent.